Triage for suspected acute Pulmonary Embolism: Think before opening Pandora's Box. Issue 6 (June 2015) - Levin, David; Seo, Joon Beom; Kiely, David G.; Hatabu, Hiroto; Gefter, Warren; van Beek, Edwin J.R.; Schiebler, Mark L.; ,
Abstract: This is a review of the current strengths and weaknesses of the various imaging modalities available for the diagnosis of suspected non-massive Pulmonary Embolism (PE). Without careful consideration for the clinical presentation, and the timely application of clinical decision support (CDS) methodology, the current overutilization of imaging resources for this disease will continue. For a patient with a low clinical risk profile and a negative D-dimer there is no reason to consider further workup with imaging; as the negative predictive value in this scenario is the same as imaging. While the current efficacy and effectiveness data support the continued use of Computed Tomographic angiography (CTA) as the imaging golden standard for the diagnosis of PE; this test does have the unintended consequences of radiation exposure, possible overdiagnosis and overuse. There is a persistent lack of appreciation on the part of ordering physicians for the effectiveness of the alternatives to CTA (ventilation–perfusion imaging and contrast enhanced magnetic resonance angiography) in these patients. Careful use of standardized protocols for patient triage and the application of CDS will allow for a better use of imaging resources.